Does alcohol use have a causal effect on HIV incidence and disease progression? A review of the literature and a modeling strategy for quantifying the effect. Issue 1 (December 2017) - Rehm, Jürgen; Probst, Charlotte; Shield, Kevin; Shuper, Paul
Abstract In the first part of this review, the nature of the associations between alcohol use and HIV/AIDS is discussed. Alcohol use has been found to be strongly associated with incidence and progression of HIV/AIDS, but the extent to which this association is causal has traditionally remained in question. Experiments where alcohol use has been manipulated as the independent variable have since helped establish a causal effect of alcohol use on the intention to engage in condomless sex. As the intention to engage in condomless sex is a surrogate measure of actual condom use behavior, which itself is linked to HIV incidence and re-infection, the causal chain has been corroborated. Moreover, there are biological pathways between alcohol use and the course of HIV/AIDS, only in part being mediated by adherence to antiretroviral medication. In the second part of the contribution, we provide suggestions on the quantification of the link between alcohol use and HIV incidence, using risk relations derived from experimental data. The biological links between alcohol use and course of HIV/AIDS are difficult to quantify given the current state of knowledge, except for an operationalization for the link via adherence to medication based on meta-analyses. The suggested quantifications are exemplified for South Africa.